2013
DOI: 10.1021/ol303434n
|View full text |Cite
|
Sign up to set email alerts
|

Direct Access to Acylated Azobenzenes via Pd-Catalyzed C–H Functionalization and Further Transformation into an Indazole Backbone

Abstract: Azobenzenes were readily acylated at the 2-position through a Pd-catalyzed C-H functionalization from simple aromatic azo compounds and aldehydes in good yields. The obtained acylated azobenzenes could be efficiently converted into the corresponding indazole derivatives in nearly quantitative yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
84
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(85 citation statements)
references
References 69 publications
0
84
0
1
Order By: Relevance
“…31 Unsubstituted azobenzene was employed for evaluating aldehyde scope, with a large variety of aromatic and aliphatic aldehydes coupling in moderate to good yield. In addition, acylation of symmetric azobenzenes bearing either electron-donating or electron-withdrawing functionality were also demonstrated.…”
Section: Aldehydesmentioning
confidence: 99%
“…31 Unsubstituted azobenzene was employed for evaluating aldehyde scope, with a large variety of aromatic and aliphatic aldehydes coupling in moderate to good yield. In addition, acylation of symmetric azobenzenes bearing either electron-donating or electron-withdrawing functionality were also demonstrated.…”
Section: Aldehydesmentioning
confidence: 99%
“…The reaction was carried out in DCE at 120 o C with tert-butyl hydroperoxide (TBHP) (4.0 equiv, 70% solution in water) as oxidant. Gratifyingly the product was obtained in 50% yield after 24 h ( [12][13][14][15][16]. Additional screening revealed that the yield decreased gradually upon increasing or decreasing temperature (Table 1, entries [17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the previous reports 12,16,17,18,19 and the above results, a tentative mechanism for TBHP-mediated reaction of aldehydes or benzyl amines with aromatic azo compounds was depicted in Scheme 3. Benzylamine (3a) first underwent oxidation, hydrolysis and the second radical oxidation by a solution of TBHP in water to form the acyl radical.…”
Section: Scheme 2 Control Experiments For Investigation Of the Mechanmentioning
confidence: 86%
“…Thus, the choice of oxidant is crucial for the reaction conditions. [22] When various oxidants were used, TBHP gave the best results, whereas a,a-dimethylbenzyl hydroperoxide (DTBP), H 2 O 2 (70 wt% in water), benzoyl peroxide (BPO), lauroyl peroxide (LPO), dicumyl peroxide (DCP), CuA C H T U N G T R E N N U N G (OAc) 2 , Ag 2 CO 3 , K 2 S 2 O 8 , and O 2 were all found to be inferior (Table 1, entries 7-15). On the other hand, the use of oxidants such as CuA C H T U N G T R E N N U N G (OAc) 2 and Ag 2 CO 3 was inefficient (Table 1, entries 12 and 13).…”
mentioning
confidence: 99%
“…More TBHP was able to oxidize the aldehydes. When the temperature was either increased or decreased, an obvious decline was observed in the yield (Table 1, entries [22][23][24][25]. Meanwhile, when we decreased the amount of PdA C H T U N G T R E N N U N G (OAc) 2 (5 mol%), the yield decreased (Table 1, entry 26).…”
mentioning
confidence: 99%